Soil quality variation associated with land cover in the Peruvian jungle of the Junín region - Carbajal Llosa, Carlos Miguel; Moya Ambrosio, Fernanda; Barja Ingaruca, Antony Marcos; Ottos Diaz, Elvis; Aguilar Tito, Cinthya; Advíncula Zeballos, Orlando; Cruz Luis, Juancarlos Alejandro; Solórzano Acosta, Richard Andi (Elsevier, 2025)
In the Junín jungle, inappropriate agricultural management practices for a long time can adversely affect soil quality. This has driven the development of multiple soil quality evaluation methods that are highly demanding in terms of economic and human resources. This study aimed to evaluate the effect of land-use change from natural ecosystems to agricultural systems by determining soil quality in the jungle of the Junin Region. Soil samples were collected between December 2021 and July 2022 in the Chanchamayo and Satipo provinces in the Junín region. Seventy-four samples were determined using stratified sampling, along with the support provided by the stacking of five spatial layers. Physical, chemical, and biological indicators, along with land cover type data from the European Space Agency (ESA) WorldCover product, were determined. A minimum data set (MDS) was established through correlation analysis, from which principal component analysis (PCA) was performed. Finally, the weighted soil quality index (SQIw) was calculated by integrating the most essential variables identified through PCA. It was found that forest cover soils had a higher SQIw than soils with crops and grassland cover. According to PCA, the soil quality variables that contributed the most are potassium (K) content and pH. It was concluded that the jungle soil quality in the Junín region is moderate to low, depending on the coverage. In addition, more significant degradation was observed in grassland-covered areas, particularly in the Chanchamayo province than in the Satipo province.